Results from an improved flowing liquid lithium limiter with increased flow uniformity in high power plasmas in EAST. (27th November 2018) - Zuo, G.Z.; Hu, J.S.; Maingi, R.; Sun, Z.; Yang, Q.X.; Huang, M.; Meng, X.C.; Xu, W.; Qian, Y.Z.; Li, C.L.; Bi, H.L.; Chen, Y.; et al.
Abstract: Significant engineering and physic progress was made by the upgrade of a flowing liquid lithium limiter (FLiLi) inserted into EAST H-mode discharges in 2016. The progress includes an improvement of liquid Li coverage uniformity, no macroscopic surface erosion by plasma materials interaction, effective removal of 55% of the discharge heat flux using high pressure He cooling during ohmic discharges, and the demonstrated ability to restart Li flow for a second experiment performed a week after the first. With increasing Li flow rate, fuel particle recycling and Fe impurity radiation gradually decreased, and plasma performance slightly improved, but there was no impact on the edge tungsten influx. No obvious Li bursts appeared during operation with up to about 4.5 MW auxiliary heating power with peak heat flux reaching ~4 MW m −2 on FLiLi. In addition, a gradual mitigation of edge localized mode (ELM) activity was observed with FLiLi operation. Finally, short-lived ELM-free phases were observed for the first time in EAST during FLiLi insertion, with increasing τ E and transient H98( y, 2)   <  2.